3D food printing: main components selection by considering rheological properties. Issue 14 (6th August 2019) - Jiang, Hao; Zheng, Luyao; Zou, Yanhui; Tong, Zhaobin; Han, Shiyao; Wang, Shaojin
Abstract: 3D printing, also referred to as additive manufacturing, offers a wide range of new processing possibilities to the food industry. This technology allows a layer by layer (bottom to top) printing of predefined slices of designed and desired objects. 3D printing potentially allows rapid manufacturing of complex objects, which are unhindered by design complexity, thus providing substantial liberty to create new and untested geometric shapes. In terms of food manufacturing, the potential that 3D food printing technologies can bring may revolutionize certain aspects of food manufacturing, providing the convenience of low-cost customized fabrication and even tailored nutrition control. The most common materials suitable for 3D food printing are carbohydrate, fat, protein, fiber and functional components. In the present study, the characteristics of raw materials or additives used during 3D printing, and requirements for estimating and improving their printing performance and self-supporting ability in extrusion-based printing regarding rheological characteristics of 3D food printing materials are reviewed. As an innovative process, 3D food printing may induce a revolution in certain areas of food manufacturing.